A Reading on Critical Regionalism in the Northern Aegean Residential Architecture: Analysis of Ancient Troy, Traditional Ayvacik Houses and SM House - Gumus, Imran; Polatoglu, Cigdem (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2020)
This study aims to investigate how the concept of critical regionalism can be instrumentalized in deciphering architectural continuity. The aim of the study is to demonstrate the dialogue that SM House has established with its geography by employing the critical regionalism approach. The main objective is to use critical regionalism to analyze SM House compared to other housing typologies in its geographical region and to reveal the relationship between the modern house and traditional and ancient houses. Visual and syntactic analyses of SM House and other houses from different times, including the ancient and traditional periods, were carried out in order to examine the concept of architectural continuity in the Northern Aegean and to evaluate the claim that SM House is a representative of local modernism. The visual analysis included analyses of plans, facades, and photographs. This method of analysis has been used to interpret spatial relations, materials, and construction techniques. Justified permeability graphs (gamma analysis) were used in space syntax analyses and have contributed to interpreting the social and cultural effects of spatial relationships. Real relative asymmetry (RRA), integration, visual integration, depth, and compactness values were used to interpret the possibilities of spatial experience and socialization offered by the houses examined and to analyze the readability of spaces. The contextual continuity and local reference of megaron, traditional, and modern houses in the Northern Aegean have been deciphered through visual and syntactic analyses. This study interprets contextual continuity as the essence of critical regionalism. The basic principles used in this study for the instrumentalization of critical regionalism included the principles of spatial experience'; local form and material'; tectonic form'; and space-culture relationship derived from interpretations of the current literature and Frampton's principles, together with the principle of alienation introduced by Tzonis & Lefaivre (1981). The five principles through which critical regionalism is interpreted are applied to the visual and syntactic analyses of houses corresponding to three different time-space periods. The critical regionalist approach uses the local materials in order to respond to aesthetic concerns and to maintain the mass balance of the building in addition to functional requirements. This approach transforms local architecture without breaking the relationship between the place and the building by enabling the implementation of new technological systems and materials together with contemporary principles. The courtyard, which was located in the entrance of the ancient house, served as the most social place of the house, while in the traditional house this function was taken on by the sofa, which was located at the entrance of the house and on the upper floor. The entrance of the house was used to socialize and gather in the ancient period, while sofas which were located on the upper floors in traditional houses functioned as closed spaces where occupants came together. In the ancient period, high-depth housing types were common in order to provide protection. The short edges of the houses were used as entrances. In SM House, which reflects the modern period, the entrance is accessed by opening a niche from the long edge of the residence as opposed to the short edge used in the ancient period. SM House offers a combination of the ancient courtyard and the traditional sofa. However, the sofa has been re-interpreted as a low-privacy space with direct access not only for residents but also for visitors. Here, the architect re-interpreted traditional and ancient codes using the principle of alienation': These data show that the changing social order, cultural transformations, and technological developments are important factors in the transformation of local elements of residential architecture. The unusual use of the local material in the SM House and the effort to communicate with visitors in addition to the residents confirm that SM House is taking a contrary approach to the traditional dwelling, which does not prioritize communication. In order to avoid dangers, the traditional house included features such as small window openings and small dimensions opened to the outdoor space; these features continued in traditional houses out of privacy concerns. In SM House, rather than traditional cultural norms, the desire to establish a strong relationship with the landscape is prioritized. Furthermore, the technological facilities incorporated into the construction of the house have been designed as outward-oriented. This house, which a family of four will use as a holiday home, has concerns independent of the spatial priorities of traditional residents. The elements that organize the place are not cultural norms, but regional references such as landscape, climate, topography, and local construction techniques. The need for defense and protection in the ancient period, a desire for privacy in the traditional period, and a preference for spatial experiences in the modern period are the main factors that influence the form of the houses. Spatial priorities varied in the relationships established with place in the three different time periods, but continuity has prevailed in the organization of space. This continuity has been made possible by local construction techniques, local materials, and topography guiding the design process. Visual analyses have found that the houses built in the three different time periods in the Northern Aegean contain the most rational solutions for their periods; syntactic analyses have shown how local and non-local subjects change and re-define the use of space. Visual and syntactic analyses of houses represented in different time periods can guide the creation of new designs that are compatible with nature, neighborhood, and context when evaluated as data sets within the critical regionalist approach. This study has shown that critical regionalism can be transformed into a method that contains data which can be integrated into the architectural design process, beyond the principles that allow for the construction of buildings to be evaluated after the construction process has been completed. The original contribution of the study to the current literature is an attempt to transform the critical regionalism approach into an analytical method through the analysis of houses built in three different time periods in the Northern Aegean. The rationale behind this method is to reveal the potential of critical regionalism as part of the design process beyond the principles of evaluation after the evaluation after the construction process.
Keywords: Aegean Region; critical regionalism; space syntax; traditional houses; vernacular; Architecture